ISO photometry of hyperluminous infrared galaxies: Implications for the origin of their extreme luminosities - Verma, A; Rowan-Robinson, M; McMahon, R; Efstathiou, A (2003)
We present 7-180μm photometry of a sample of hyperluminous infrared galaxies (HyLIGs) obtained with the photometer and camera mounted on the Infrared Space Observatory (ISO). We have used state-of-the-art' radiative transfer models of obscured starbursts and dusty tori to model their broadband spectral energy distributions (SEDs). We find that IRAS F00235+1024, IRAS F14218+3845 and IRAS F15307+3252 require a combination of starburst and AGN components to explain their mid to far-infrared emission, while for TXS0052+471 a dust torus model alone is sufficient. For IRAS F00235+1024 and IRAS F14218+3845 the starburst component is the predominant contributor whereas for IRAS F15307+3252 the dust torus component dominates. The implied star formation rates (SFR) estimated from the starburst infrared luminosities are dM*,all/dt > 1000M⊙yr-1h50-2 and are amongst the highest SFRs estimated to date. We also demonstrate that the well-known radio-FIR correlation observed for extragalactic sources extends into both higher radio and infrared power than previously investigated. The relation for HyLIGs has a mean q value of 1.94. The results of this study imply that better sampling of the IR SEDs of HyLIGs may reveal that both AGN and starburst components are required to explain their emission from the NIR to the sub-millimetre.